Comparison of Water Velocity of Physical and Numerical Modelling Analysis on a Downscale Spillway - Nurhikmah F.; Zawawi M.H.; Hassan N.H.; Zahari N.M. (Springer Science and Business Media Deutschland GmbH, 2025)
The study on the effect of velocity on the spillway was done conducted using physical and numerical model analysis. The 1:40 scale physical model was developed, where the velocity was measured in fourteen measurements points for three different velocity flows. Numerical modelling was analysed using Computational Fluid Dynamic (CFD) to compare the accuracy of the physical model analysis. Results from the study indicate that the maximum percentage difference between the physical model and numerical analysis in velocity values do not exceed 10% for all three cases. Point Q3 shows the highest value of velocity with 0.036m/s for the physical model and 0.039m/s for numerical modelling. The percentage of difference at point Q3 for numerical modelling and the physical model result is 7.69%. Meanwhile, points P5 and S5 indicate the lowest value of velocity, where the physical model and numerical modelling shows the same which is 0.006m/s. The percentage of difference at points P9 and S5 for numerical modelling and the physical model result is 0.00%. It can be concluded that the velocity flow is higher at the energy dissipater parts compared to the stilling basin area due to the dispersion of water flow along the spillway. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd 2024.